Focus groups exploring American consumer perspectives on contemporary poultry production reveal critical insights to educate sustainable practices for producers - Dewi, Grace; Smith, Chery; Martin, Wayne; Venkitanarayanan, Kumar; Kollanoor Johny, Anup (Frontiers in Sustainable Food Systems, 2024)
Ensuring sustainability in poultry production is complex and requires a multifaceted approach that considers human health and food security, bird health, the environment, and society. Consumers are critical stakeholders, yet their growing disconnection from agriculture production practices complicates efforts to achieve more sustainable systems. This study aims to gain insights into consumers' attitudes toward poultry and perceptions of contemporary production methods. Exploration of consumer perspectives would offer valuable insights that could educate producers on the priorities of the target market and make informed decisions about embracing practices to increase the sustainability of their operations. In this context, eight focus group discussions (FGDs) were conducted with 54 multicultural participants who consume chicken and reside in Minnesota, USA. The major themes that emerged from the FGDs include (1) purchasing and consumption habits, (2) concerns regarding production methods, (3) the impact of social, religious, and cultural factors, (4) familiarity with poultry production practices, and (5) the importance of educating consumers and producers. The study revealed that convenience, affordability, and health benefits are positive drivers of poultry consumption. While participants exhibited a greater preference for the flavor of dark (leg and thigh) meat, they often chose breast meat for its convenience, ease of preparation, and perceived health benefits. Concern for human health tended to take precedence over ethical claims associated with animal welfare. Furthermore, misconceptions emerging from skepticism and unfamiliarity with regulations and the labeling of poultry products may deter the acceptability of higher costs. Many participants identified knowledge gaps and sought science-based information from reliable sources. They conveyed the necessity of outreach and education for consumers in more engaging and accessible forms of communication. The well-established reputation of poultry as a healthy, convenient, and affordable source of protein is the main driver for its consumption. Learning the attributes they believe are significant and underlying motivations or obstacles to consumption can be beneficial in developing effective strategies to promote the adoption of sustainable practices. Enhancing consumer understanding of sustainable poultry production could influence their acceptance and readiness to absorb the additional costs associated with it.